2019
DOI: 10.1523/jneurosci.3172-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Adaptation Reveals a Suboptimal Decoding of Orientation Tuned Populations in the Mouse Visual Cortex

Abstract: Sensory information is encoded by populations of cortical neurons. Yet, it is unknown how this information is used for even simple perceptual choices such as discriminating orientation. To determine the computation underlying this perceptual choice, we took advantage of the robust visual adaptation in mouse primary visual cortex (V1). We first designed a stimulus paradigm in which we could vary the degree of neuronal adaptation measured in V1 during an orientation discrimination task. We then determined how ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…Stimulus orientation is a fundamental feature that is robustly encoded in the visual system of most species, including mouse V1 and the HVAs [18,19]. While V1 is known to be required for tasks involving discrimination of stimulus orientation [30,3234], it is not known which, if any, higher visual areas are necessary for the perception of this distributed representation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stimulus orientation is a fundamental feature that is robustly encoded in the visual system of most species, including mouse V1 and the HVAs [18,19]. While V1 is known to be required for tasks involving discrimination of stimulus orientation [30,3234], it is not known which, if any, higher visual areas are necessary for the perception of this distributed representation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we trained mice to perform a go/no-go orientation discrimination task ( Figure 2A , [33,34]). In this task, the mice press a lever to initiate the trial and trigger the repeated presentation of a vertically oriented distractor (0°, 2-10 distractors, 100 ms duration, 250-750 ms inter-stimulus interval (ISI)) followed by the presentation of a target orientation (8-90° counter-clockwise difference from the distractor).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to test the physiological similarity between electrically-evoked and visually-evoked responses, we tested whether electrically-evoked responses adapted to visual stimuli. Previous work has shown that the neural response to a visual stimulus is reduced when the stimulus is repeated (Jin et al, 2019). This 'adaptation' of the neural response has been used to measure the similarity of neural responses to visual stimuli (Leopold et al, 2001).…”
Section: Using Adaptation To Test the Physiological Relevance Of Elecmentioning
confidence: 99%
“…Trials were separated by 4500-5000ms intertrial interval (ITI). ISI and ITI values were chosen based on previous studies (Jin et al, 2019) . Each trial type was repeated 30 times and the trial order was random.…”
Section: Adaptation Experimentsmentioning
confidence: 99%